Three-Dimensional CFD modelling and analysis of the thermal entrainment in open refrigerated display cabinets - Gaspar, Pedro Dinis (2008)
This study presents a three-dimensional Computational Fluid Dynamics (CFD) simulation of the air flow pattern and the temperature distribution in a refrigerated display cabinet. The thermal entrainment is evaluated by the variations of the mass flow rate and thermal power along and across the air curtain considering the numerical predictions of abovementioned properties. The evaluation on the ambient air velocity for the three-dimensional (3D) effects in the pattern of this type of turbulent air flow is obtained. Additionally, it is verified that the longitudinal air flow oscillations and the length extremity effects have a considerable influence in the overall thermal performance of the equipment. The non uniform distribution of the air temperature and velocity throughout the re-circulated air curtain determine the temperature differences in the linear display space and inside the food products, affecting the refrigeration power of display cabinets. The numerical predictions have been validated by comparison with experimental tests performed in accordance with the climatic class n.º 3 of EN 441 Standard (Tamb = 25 ºC,φamb = 60%; vamb = 0,2 m s-1). These tests were conducted using the point measuring technique for the air temperature, air relative humidity and air velocity throughout the air curtain, the display area of conservation of food products and nearby the inlets/outlets of the air mass flow.